Injection-driven fracture instability in granite : mechanism and implications - Ji, Yinlin (2021)
An unprecedented increase in earthquakes associated with hydraulic stimulation has been recognized as a major barrier to the development of enhanced geothermal systems. However, the mechanism of injection-induced seismicity remains enigmatic. Here we simulate the critical stress states of sawcut and natural fractures, and examine the fracture instabilities due to fluid injection. We shed light on fluid pressure heterogeneity, injection-induced fracture instability, acoustic emission characteristics and fracture surface evolution. We find that injection-induced fracture instability is strongly dependent on fluid pressure heterogeneity and fracture surface heterogeneity. High injection rates can induce a high fluid overpressure ratio in the sawcut fracture, promoting the rupture of fracture extending into the unpressurized area. The instability of the natural fracture is due to the near-uniform reduction in effective normal stress associated with a low fluid overpressure ratio. Our data indicate that maintaining a low fluid overpressure ratio during injection activities could confine the rupture of fracture within the pressurized area. A turning point of the total moment release may be used as a reference to optimize the fluid injection strategy. The seismic response of rock fracture could be modified by changing fluid pathways between the injection borehole and the fracture and by evolving surface roughness of the fracture within the stimulated volume.